A Novel Synthesis of Some Isomeric Isoxazoles - Thakare, S.S.; Doshi, A.G. (Asian Journal of Chemistry, 2010)
β-(2'-Furyl)-acrylophenone dibromide (Ia-c) react with hydroxylamine hydrochloride in pyridine to give 3-(2"-hydroxy-3"-substituted- 5" -chlorophenyl)-5-(2' -furyl)-isoxazoles (IIa-c) while in methanol the corresponding 3-(2' -furyl)-5-(2" -hydroxy-3" -substituted- 5"-chlorophenyl) isoxazoles (IIIa-c) are obtained contrary to the isomerization of isoxazoles (IIa-c) in pyridine.